2016
DOI: 10.3109/09513590.2016.1161741
|View full text |Cite
|
Sign up to set email alerts
|

The impact of unilateral salpingectomy on antral follicle count and ovarian response in ICSI cycles: comparison of contralateral side

Abstract: The study suggests that salpingectomy is not associated with detrimental effects on AFC and ovarian response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The surgical removal of hydrosalpinx prior to IVF improves PRs and reproductive outcomes. 78 In addition, salpingectomy does not affect the ovarian response, nor reduces the antral follicle count. 79 Laparoscopic salpingectomy is the optimal surgical approach; therefore, it should be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical removal of hydrosalpinx prior to IVF improves PRs and reproductive outcomes. 78 In addition, salpingectomy does not affect the ovarian response, nor reduces the antral follicle count. 79 Laparoscopic salpingectomy is the optimal surgical approach; therefore, it should be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al suggested that IVF-ET patients who had a previous unilateral salpingectomy required higher gonadotropin (Gn) doses and longer stimulation duration when undergoing a controlled ovarian stimulation (COS) compared to patients who had not undergone salpingectomy [8]. However, some investigators showed that there was no significant influence on ovarian reserve, ovarian response, or the number of retrieved oocytes before and after salpingectomy [9][10][11][12][13][14][15][16]. With advancing female age, declines in number and quality of oocytes are the primary reasons for decreasing IVF outcomes, especially in terms of live birth rates [17].…”
Section: Introductionmentioning
confidence: 99%